SHOCK ANAFILAKSIS AKIBAT ANESTESI LOKAL MENGGUNAKAN LIDOCAINE - Maria Martina Nahak (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2013)
Drug is a compound or product using for diagnostic, profilaxis or therapy to give benefits for patients but some times there is a side efect of this drug called adverse drug reaction. Lidocaine is o local onaetheticum using by lopical or parenteral to block lhe nerve before minor surgery or tooth extraction. One of the side effect of this drug is presenting of type one of hypersensitivity reaction called anaphylaxis shock which is manifestation as smooth muscle spasm of respiratory and gastrointestinal tract, vasodilation, and increase of vascular vermiability.The importance way to manage an anaphylacted patients is: immediately repair the vital signs of patients, do against the mediator action, prevention the releasing of mediator agent and continuing to controle the vital signs of patients. The conclusion is: the incidence of anaphylaxis shock caused by lidocaine is less than 1%, so the clinician must be ready to manage this incidence. Before using this drug clinician has to do good anameses before treatment, prepare all medicine and equipment to face this incidence, and ready to manage this case if happen.